PENGARUH PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP PRESTASI BELAJAR AQIDAH AKHLAK SISWA KELAS VIII DI SMP MUHAMMADIYAH BOARDING SCHOOL PROF HAMKA MADIUN 2024/2025 - Agus Budianto; Nur Hidayah (STKIP Pesisir Selatan, 2025)
This study examines the influence of TikTok social media usage on learning achievement in the Aqidah Akhlak subject among eighth-grade students at SMP Muhammadiyah Boarding School (MBS) Prof Hamka Madiun in the 2024/2025 academic year. A quantitative correlational approach was employed with 31 students as respondents. Data were collected using a TikTok usage questionnaire (a validated and reliable instrument) and documentation of students’ Aqidah Akhlak report scores. Data analysis involved descriptive statistics and simple linear regression, preceded by classical assumption tests (normality and linearity). The results indicated that TikTok usage among students was high (55% of students), while their Aqidah Akhlak performance was generally moderate (39% of students in the medium category). Regression analysis revealed a significant positive influence of TikTok usage on learning achievement (r = 0.813, p < 0.05). TikTok usage accounted for approximately 66% of the variance in Aqidah Akhlak scores. In conclusion, the use of TikTok has a significant positive effect on students’ learning achievement in Aqidah Akhlak. Students who more frequently engage with TikTok—especially for educational content—tend to achieve higher academic performance in that subject. It is suggested that TikTok be utilized as an innovative learning medium under proper guidance to enhance learning outcomes.